The role of work in gender identity, stress and health in low-income, middle-aged African-American men. (28th December 2020) - Robinson, Dean; Valdez, Luis; Scott, Lamont; Buchanan, David
Summary: Although progress has been made in reducing disparities in life expectancy, addressing the persistence of health inequities by race remains a high priority for public health professionals. The purpose of this research was to refine a minority stress model (MSM) by identifying previously unrecognized factors contributing to stress and chronic disease health disparities among low-income middle-aged African-American men. Using a Community-Based Participatory Research approach, we conducted semi-structured individual health interviews with 42 low-income middle-aged African-American men in a mid-size New England city. The interviews focused on the participants' perceptions of the causes of health disparities. Four major themes emerged from the analysis: the positive aspects of work, both financial and symbolic; and the negative repercussions of not working, both financial and symbolic in terms of a sense of self-respect. On an instrumental level, working men can support their family, be physically active and find social support. Symbolically, work provides a positive sense of identity as a man; it offers both social- and self-respect; it provides discipline and a sense of gratitude. Conversely, the lack of work is a significant source of stress, stemming both from the inability to support one's family and from having nothing to do, which lead to depression, low self-esteem, suicidal ideation and anger. With no perceived viable routes to socially approved roles, many low-income men of color succumb to internalizing a negative identity. This research demonstrates a clear link between structural problems with the US economy and harms to sense of identity among low-income, middle-aged African-American men.